2022
DOI: 10.3390/ijms23137138
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the MicroRNA Cargo of Extracellular Vesicles Isolated from a Pulmonary Tumor-Draining Vein Identifies miR-203a-3p as a Relapse Biomarker for Resected Non-Small Cell Lung Cancer

Abstract: In resected non-small cell lung cancer (NSCLC), post-surgical recurrence occurs in around 40% of patients, highlighting the necessity to identify relapse biomarkers. An analysis of the extracellular vesicle (EV) cargo from a pulmonary tumor-draining vein (TDV) can grant biomarker identification. We studied the pulmonary TDV EV-miRNAome to identify relapse biomarkers in a two-phase study (screening and validation). In the screening phase, a 17-miRNA relapse signature was identified in 18 selected patients by sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Han et al isolated several miRNAs in extracellular vesicles (EV) from pulmonary tumour drainage veins (TDVs) and identified miR-203a-3p as a recurrence marker in the 18-patient screening cohort. They further verified that miR-203a-3p was a prognostic indicator for unfavourable TTR in the 70-patient validation cohort [ 129 ].…”
Section: Resultsmentioning
confidence: 81%
“…Han et al isolated several miRNAs in extracellular vesicles (EV) from pulmonary tumour drainage veins (TDVs) and identified miR-203a-3p as a recurrence marker in the 18-patient screening cohort. They further verified that miR-203a-3p was a prognostic indicator for unfavourable TTR in the 70-patient validation cohort [ 129 ].…”
Section: Resultsmentioning
confidence: 81%
“…It can also play a role as an oncogene by promoting drug resistance, proliferation, migration, and invasion [ 45 , 46 , 47 ]. In one study, miR-203a-3p was found to be the most highly expressed miRNA in extravesicular vesicles that were isolated from the pulmonary tumor-draining vein of patients with NSCLC, and this molecule was associated with tumor relapse [ 48 ]. Finally, miR-141-3p also plays both tumor-suppressive and tumor-supportive roles.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, EV‐miR‐378 upregulation has been reported to indicate lymphatic metastasis in NSCLC [ 19 ]. EV‐miR‐203a‐3p was also shown to be significantly increased in lymph node‐positive NSCLC patients [ 20 ]. Moreover, uregulated EV‐derived circular RNAs and long non‐coding RNAs, such as circR‐0056285 and AGAP2 antisense RNA 1 (AGAP2‐AS1), have been explored to diagnose lymphatic metastasis in NSCLC [ 21 , 22 ].…”
Section: Molecular Mechanisms Of Lymphatic Metastasis and Lymphangiog...mentioning
confidence: 99%